Chronic traumatic diaphragmatic hernia: A case report - Rudy Jhair Zambrano Morales (Universidad Técnica de Manabí, 2017)
A diaphragmatic hernia is a very rare pathology, and clinical suspicion is needed for its diagnosis, and in cases of closed trauma it is much more frequently. For a correct diagnosis in chronic cases we should focus the importance of personal record and imaging studies, because the signs and symptoms may go unnoticed. In this sense, the objective is to describe the main clinical manifestations a diaphragmatic hernia, its approach and, diagnosis. The patient went to the Portoviejo Medical Clinic for a different reason and when performing a chest x-ray, the diagnosis of chronic diaphragmatic hernia was outlined. Currently, the treatment of choice is laparoscopy, but the patient presented complications and had to undergo an open surgical procedure. Conclusions: in order to reduce mortality and complications, a correct diagnosis must be made, recognizing by signs, symptoms and images if we are facing an acute or chronic condition; and always take into account personal record, as that can give the clue that helps in the diagnosis and early treatment.